PENEMPATAN LIGHTNING ARRESTER DAN WATAK PERLINDUNGAN YANG DIBERIKAN PADA PERALATAN - , M.YOZA ACIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Arrester installation in electrical system need to consider the placement that provides the best protection for the protected equipment. This paper considers the placement of arrester in relation with the influence of arrester phase and grounding cable placement in the protected equipment, by performing a wide variety of placement testing, as well as variations in cable length and then by comparing the effect given to the protected equipment. Results showed that voltage received by the protected equipment was the sum of arrester residual voltage and the voltage at arrester phase and grounding cable. Voltage rise received by the protected equipment originated from arrester cable is the product of steepness level surge current and inductance which is in arrester phase and grounding cable that connect the protected equipment. Having compared the effect of voltage rise, SiC arrester was worse than ZnO arrester due to the structure of the SiC arrester which had a spark gap. In addition there are things needed to be considered in certain circumstances, an increase in voltage due to the wave reflection causing a voltage rise by an average of 14.39% in equipment protected byZnO arrester, and an average of 20.13% for equipment protected by SiC arrester . Installation is the best when arrester cable is kept as short as possible, the connection phase equipment either installed at arrester terminals, while grounding connection is not directly made at the protected equipment terminal, but rather paralleled with cable.